Meteorological characteristics changes in equatorial latitude associated with solar activity - Lal, M.; Subramanian, M. V. (My University, 2007)
We have made an attempt to study the influence of geomagnetic storm on the equatorial upper troposphere temperature and wind variability. The NCEP â€” Re analysis data has been taken as an input for the present study. The Dst index has been taken as an indicator of the onset of magnetic storm and its strength. The change in the upper tropospheric temperature and wind variation over equatorial latitude is found to be sensitive to the onset of geomagnetic storm. The superpose epoch analysis shows the changes in temperature and wind velocity after 3 days of the onset of the event. The influence of QBO phase has been found to be effective on the temperature as well as vertical wind velocity variation. The change in the magnitude is also sensitive to the solar activity condition. The increase in the temperature during Wâ€ phase of QBO and vice versa has been observed after the onset of the event. The horizontal wind velocity shows the influence of magnetic storm on the continent as well as over the Ocean. One of the possible mechanism is the geomagnetic activity influences equatorial tropospheric meteorological parameters via the stratosphere.
Keywords: Geomagnetic storms; Storms and substorms; Density; Atmospheric temperature; Troposphere; Solar activity; Meteorological